THE EFFECT OF GROUP COUNSELING WITH A RATIONAL EMOTIVE BEHAVIOR THERAPY APPROACH IN OVERCOMING SMARTPHONE ADDICTION IN CLASS X STUDENTS OF PUBLIC HIGH SCHOOL 1 SIPIROK - Yana Yupita Sitompul; Nurussakinah Daulay (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
Smartphone addiction is becoming a problem for students in the technological era. The teenagers (students) need guidance from adults (teachers or students) in this case. The purpose of this study is to determine the effect of group counseling with Rational Emotive Behavior in minimizing smartphone addiction. The background of this study specifically is the topic of research at SMA Negeri 1 Sipirok, namely with 35 students in class X TA. 2022/2023, to test how high the level of smartphone dependence in students before, then after using the REB approach. This type of research is Guidance and Counseling Action Research (PTBK) which was carried out in two periods. Data analysis was done quantitatively by observation and questionnaire. According to the findings of this study, the level of smartphone addiction of class X SMA Negeri 1 Sipirok students at the time of the pre-test was 14 students (38.9%), 2 students were in the very high category and 12 students were in the high category. In addition, group counseling was conducted during Cycle I with the REB approach, and during questionnaire filling, 1 student (7.1%) was in the very high category that is still a smart addict, and 8 students were in the very high category in cycle II, there were 4 students (28.6%) in the high class still addicted to smartphones, 2 students in the middle class, 7 students in the low class, and 1 student in the very low class. In this way, it is assumed that the level of smartphone dependence among class X students of SMA 1 Sipirok decreased after the REBT group approach counseling.